Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1016/s1010-7940(01)00774-6
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations on haemodynamics during physiological stress conditions following ‘double-orifice’ mitral valve repair

Abstract: This study indicates that though effective mitral valve competence is achieved in the majority of operated patients, DO repair may induce impaired diastolic mitral dynamism in some cases, particularly during exercise conditions. Further investigations are required to thoroughly elucidate the overall mechanics of a DO valve, especially at strenuous cardiocirculatory states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Several studies showed that mean and peak transmitral valve gradients are slightly higher during exercise in patients with degenerative MR who have undergone edge-to-edge technique with or without annuloplasty ring 26 27. A slightly lower postoperative reduction in LAVi and a slightly higher postoperative transmitral mean pressure gradient were observed in our study in these patients than in patients with other types of repair.…”
Section: Discussionsupporting
confidence: 48%
“…Several studies showed that mean and peak transmitral valve gradients are slightly higher during exercise in patients with degenerative MR who have undergone edge-to-edge technique with or without annuloplasty ring 26 27. A slightly lower postoperative reduction in LAVi and a slightly higher postoperative transmitral mean pressure gradient were observed in our study in these patients than in patients with other types of repair.…”
Section: Discussionsupporting
confidence: 48%
“…LVOTO is caused by systolic anterior motion of the anterior mitral leaflet and may occur in presence of excess tissue of the mitral leaflets and inadequate ring sizing, resulting in a "too small ring for a too large anterior leaflet" [2]. Impaired diastolic transmitral flow, with significant increase in transvalvular pressure gradient and in sPAP at peak exercise, have recently been reported in patients treated by the "double-orifice" technique [25]. Impaired diastolic annular dynamics and hampered exercise-related increase in left ventricular ejection fraction can occur when a rigid ring is employed [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…TTE and TEE are the most usual and useful tools to evaluate intra- and post-operative results [5-17], while exercise TTE is usually employed to evaluate valvular dynamics and function under stress conditions [25,26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations